Trisomy 13 mosaicism syndrome with atypical plurimalformative phenotype - Cristina-Crenguta Albu; Dinu-Florin Albu; Stefan-Dimitrie Albu (International Journal of Medical Research and Review, 2019)
Introduction: Orofacial clefts are important congenital malformations of the lip, palate, or both caused by complex genetic and environmental factors. Aims andObjectives: The present study aims to highlight the phenotypic heterogeneity of trisomy 13 mosaicism.Material and Methods: We present one clinical case of a 30-year-old, Caucasian woman who is pregnant for the first time.Techniques of work study: anamnesis, clinical examination, serological tests for Toxoplasmosis, Rubeola, CMV and Herpes, ultrasound examination at 20 weeks gestation with General Electric Echographe Voluson E10 BT18, amniocentesis, fetal chromosome analysis and genetic counseling.Results: Ultrasound examination showed a viable singleton fetus with intra-uterine growth restriction, oligohydramnios, bilateral cleft lip and cleft palate, hypoplastic nasal bone and bilateral polycystic kidneys. Amniocentesis was done, and the fetal chromosomal analysis revealed a fetus with 46, XY/47, XY,+13 mosaic karyotype. After a complex genetic counselling the parents opted, to terminate the pregnancy. The autopsy confirm the prenatal ultrasound diagnosis.Conclusion: Routine ultrasound examination during pregnancy and specific genetic testing are essential for the early prenatal detection of major structural fetal anomalies associated with rare genetic chromosome syndromes.